Serum Parathyroid Hormone and 25‐Hydroxyvitamin D Concentrations and Risk of Incident Heart Failure: The Multi‐Ethnic Study of Atherosclerosis. Issue 6 (2nd December 2014) - Bansal, Nisha; Zelnick, Leila; Robinson‐Cohen, Cassianne; Hoofnagle, Andy N.; Ix, Joachim H.; Lima, Joao A.; Shoben, Abigail B.; Peralta, Carmen A.; Siscovick, David S.; Kestenbaum, Bryan; de Boer, Ian H.
Abstract : Background: Heart failure (HF) is common and is associated with high mortality. We aimed to determine associations of serum parathyroid hormone (PTH) and 25‐hydroxyvitamin D (25[OH]D) with incident HF and left ventricular mass. Methods and Results: Among 6459 participants in the community‐based Multi‐Ethnic Study of Atherosclerosis, all of whom were free of prevalent clinical cardiovascular disease, we measured serum concentrations of PTH and 25(OH)D at the baseline examination. In longitudinal analyses, we tested associations of PTH and 25(OH)D with incident HF events, adjudicated by a panel of physicians. In cross‐sectional analyses of a subset of 4763 participants, we tested associations of PTH and 25(OH)D with left ventricular mass, measured by cardiac magnetic resonance imaging at baseline. Multivariable Cox proportional hazard and linear regression models were adjusted for demographics, physical examination measures, comorbidity, kidney function, and other mineral metabolism markers. Mean age was 62 years and 53% of participants were female. There were 180 incident HF events over a median (interquartile range) follow‐up time of 8.46 (7.67 to 8.63) years. Compared with participants with PTH <65 pg/mL, PTH ≥65 pg/mL was associated with a 50% greater risk of incident HF (95% CI: 3% to 210%) and a 5.3 g higher left ventricular mass (95% CI: 2.6, 7.9 g). In contrast, there was no association of 25(OH)D with risk of incident HF or elevated left ventricular mass. Conclusions: In a racially/ethnically diverse population without prevalent cardiovascular disease, higher serum PTH concentration was associated with increased left ventricular mass and increased risk of incident HF. Further studies should be pursued to determine whether PTH excess may be a modifiable risk factor for HF.